Multifaceted Bullying of Children with Disabilities: Challenges from Peers, Educators, and Parents - Chandra, Saumya (International Journal of Rehabilitation and Special Education (IJRSE), 2026)
Bullying remains a pervasive challenge in educational settings, disproportionately affecting children with disabilities. This study explores the multifaceted nature of bullying experienced by these children, examining the roles of peers, educators, and parents in perpetuating or mitigating such behaviors. It incorporates informal observations, qualitative interviews, and case studies to provide a comprehensive understanding of the bullying dynamics. The findings highlight the prevalence of bullying, including social exclusion, verbal abuse, and implicit bias from authority figures. The study underscores the compounding effects of these experiences on the emotional, cognitive, and social development of children with disabilities. The analysis identifies systemic barriers within educational institutions that contribute to the persistence of bullying, including inadequate teacher training, lack of inclusive policies, and limited parental awareness. The study proposes evidence-based interventions, structured peer support programs, educator sensitization workshops, and parental engagement initiatives, to foster an inclusive and supportive environment for children with disabilities. The research underscores the urgency of a multi-stakeholder approach to effectively combat bullying and promote equity in educational settings.